The effects of uphill vs. level-grade high-intensity interval training on VO2max, Vmax, VLT, and Tmax in well-trained distance runners - Ferley, D. D.; Osborn, R. W.; Vukovich, M. D. (The Journal of Strength and Conditioning Research, 2013)
Uphill running represents a frequently used and often prescribed training tactic in the development of competitive distance runners but remains largely uninvestigated and unsubstantiated as a training modality. The purpose of this investigation included documenting the effects of uphill interval training compared with level-grade interval training on maximal oxygen consumption (VO2max), the running speed associated with VO2max (Vmax), the running speed associated with lactate threshold (VLT), and the duration for which Vmax can be sustained (Tmax) in well-trained distance runners. Thirty-two well-trained distance runners (age, 27.4 ± 3.8 years; body mass, 64.8 ± 8.9 kg; height, 173.6 ± 6.4 cm; and Vo2max, 60.9 ± 8.5 ml/min/kg) received assignment to an uphill interval training group (GHill = 12), level-grade interval training group (GFlat = 12), or control group (GCon = 8). GHill and GFlat completed 12 interval and 12 continuous running sessions over 6 weeks, whereas GCon maintained their normal training routine. Pre- and posttest measures of VO2max, Vmax, VLT, and Tmax were used to assess performance. A 3 × 2 repeated measures analysis of variance was performed for each dependent variable and revealed a significant difference in Tmax in both GHill and GFlat (p < 0.05). With regard to running performance, the results indicate that both uphill and level-grade interval training can induce significant improvements in a run-to-exhaustion test in well-trained runners at the speed associated with VO2max but that traditional level-grade training produces greater gains.